A simplified reliability estimation method for pile-supported wharf on the residual displacement by earthquake. Issue 129 (February 2020) - Nagao, Takashi; Lu, Panpan
Abstract: Pile-supported wharves undergo lateral displacement as well as structural damage due to earthquakes. Therefore, residual displacement and structural safety assessment are necessary for earthquake-resistant design of pile-supported wharves. This study introduces a simplified reliability estimation method for pile-supported wharves, involving the residual displacement caused by earthquakes and the variation of earthquake ground motions. As the residual displacement of wharves is strongly affected by the deformation of subsoil caused by earthquakes, a soil-structure system finite element earthquake response analysis was performed. To reduce the computational load for the evaluation of a probability distribution of residual displacement, a first-order second-moment method estimating the probabilistic response of structures with a small number of trials was applied. Thefinite element analyses demonstrate that the summed squared Fourier amplitudes (SSFAs) of the input seismic motion for a cumulative probability frequency band better estimated the residual displacement. A simplified reliability estimation method utilizing three results of finite element analyses is proposed following the demonstration of its applicability. Highlights: Sum of squared Fourier amplitude of waveform for evaluating residual displacement. Three results of FEA for probability distribution estimation of residual displacement. Reliability index estimation by use of First-order second-moment method.